2003
DOI: 10.1101/lm.58803
|View full text |Cite
|
Sign up to set email alerts
|

Complex Effects of NMDA Receptor Antagonist APV in the Basolateral Amygdala on Acquisition of Two-Way Avoidance Reaction and Long-Term Fear Memory

Abstract: Although much has been learned about the role of the amygdala in Pavlovian fear conditioning, relatively little is known about an involvement of this structure in more complex aversive learning, such as acquisition of an active avoidance reaction. In the present study, rats with a pretraining injection of the N-methyl-D-aspartate (NMDA) receptor antagonist, 2-amino-5-phosphonopentanoic acid (APV), into the basolateral amygdala (BLA) were found to be impaired in two-way active avoidance learning. During multitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…The amygdala is critically involved in both cued and contextual fear conditioning (Phillips and LeDoux, 1992) and contains NMDARs (Maren et al, 1996). In support, direct infusion of APV into the amygdala disrupted acoustic fear potentiated startle and fear conditioning (Fanselow and Kim, 1994; Fanselow et al, 1994; Kim et al, 1991; Laurent and Westbrook, 2009; Maren et al, 1996; Miserendino et al, 1990; Savonenko et al, 2003). It is also possible that the observed deficit in cued fear conditioning was due to the effects of MK-801 in other brain regions, including the hippocampus.…”
Section: Discussionmentioning
confidence: 85%
“…The amygdala is critically involved in both cued and contextual fear conditioning (Phillips and LeDoux, 1992) and contains NMDARs (Maren et al, 1996). In support, direct infusion of APV into the amygdala disrupted acoustic fear potentiated startle and fear conditioning (Fanselow and Kim, 1994; Fanselow et al, 1994; Kim et al, 1991; Laurent and Westbrook, 2009; Maren et al, 1996; Miserendino et al, 1990; Savonenko et al, 2003). It is also possible that the observed deficit in cued fear conditioning was due to the effects of MK-801 in other brain regions, including the hippocampus.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, in this study, we used the Morris water maze test to evaluate cognitive function instead of the shuttle avoidance test so that we could focus on hippocampus function. The shuttle avoidance test (also called the 2-way active avoidance test) is considered to measure nondeclarative memory and relies on both classic fear conditioning and instrumental conditioning 21 and is often thought to be primarily striatum dependent. 22 On the other hand, a spatial working memory task, such as the Morris water maze test, depends on hippocampus function, [23][24][25] and we hypothesized that an even lower dose of telmisartan treatment would moderate hippocampal activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that active shuttle avoidance task measures nondeclarative memory (Savonenko et al, 2003) and is hippocampus independent. Another possible explanation for the results is that, while the amygdala becomes less involved, other brain areas such as the caudate nucleus (Packard et al, 1994) but not the hippocampus become involved.…”
Section: Differential Activation Level Of Both Erk2 and Creb In The Blamentioning
confidence: 99%